FINANCIAL CRISIS IN ASIA: ITS GENESIS, SEVERITY AND IMPACT ON POVERTY AND HUNGER. (November 2013) - Imai, Katsushi S.; Gaiha, Raghav; Thapa, Ganesh; Annim, Samuel Kobina; Lawson, David; Amann, Edmund
Abstract Building on the recent literature on finance, growth and hunger, we have examined the experience of Asian countries over the period 1960–2010 by dynamic and static panel data models. We have found evidence favouring a positive role of finance—defined as private credit by banks—on growth of GDP and agricultural value added. Private credit as well as loans from the World Bank significantly reduces undernourishment, whereas remittances and loans from microfinance institutions appear to have a negative impact on poverty. Our empirical evidence shows that growth performance was significantly lower during the recent global financial crisis than non‐crisis periods, although the severity is much smaller during the recent financial crisis than Asian financial crisis. Copyright © 2013 John Wiley & Sons, Ltd.